2019
DOI: 10.1002/prep.201900211
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Ferrates (NiFe2O4, ZnFe2O4 and CoFe2O4) on the Thermal Decomposition of Ammonium Perchlorate

Abstract: Three kinds of ferrates (NiFe2O4, ZnFe2O4 and CoFe2O4) were prepared via the facile solvothermal method and characterized using SEM, TEM, XRD, XPS, FT‐IR and BET instruments. The NiFe2O4, CoFe2O4 and ZnFe2O4 particles possess hollow structure with average particle size of 70, 220 and 360 nm, respectively. The catalytic performance of the ferrates for AP thermal decomposition were studied using DSC and TG‐DTG methods, and the decomposition mechanism of AP were suggested. The catalytic effects of different ferra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…[7,9,10] Because of this drawback of physical method, different catalysts are being widely used to achieve lower thermal decomposition of AP. Catalysts like metals, [11,12] metal oxides, [6,[13][14][15][16][17] metal alloys, [8,[18][19][20][21] carbon supported catalysts, [22][23][24][25][26][27][28] metal hydroxides [29][30][31] are most investigated catalysts for achieve lower thermal decomposition temperature of AP via optimizing its decomposition route. AP decomposition undergoes two steps: one is LTD, low thermal decomposition in the range 280 °C-320 °C temperature that reveal gas products like perchlorate (HClO 4 ) and ammonia (NH 3 ); another is HTD, high thermal decomposition in the range 320 °C-450 °C temperature that reveal retreated gas mixtures of N 2 O, NO, O 2 and HCl, and release high amount of heat with ignition thrust.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7,9,10] Because of this drawback of physical method, different catalysts are being widely used to achieve lower thermal decomposition of AP. Catalysts like metals, [11,12] metal oxides, [6,[13][14][15][16][17] metal alloys, [8,[18][19][20][21] carbon supported catalysts, [22][23][24][25][26][27][28] metal hydroxides [29][30][31] are most investigated catalysts for achieve lower thermal decomposition temperature of AP via optimizing its decomposition route. AP decomposition undergoes two steps: one is LTD, low thermal decomposition in the range 280 °C-320 °C temperature that reveal gas products like perchlorate (HClO 4 ) and ammonia (NH 3 ); another is HTD, high thermal decomposition in the range 320 °C-450 °C temperature that reveal retreated gas mixtures of N 2 O, NO, O 2 and HCl, and release high amount of heat with ignition thrust.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Previous work suggested that metal ferrites have high catalytic activity for the decomposition of AP. [8,21,32,33] However, the studies that focus on the AP decomposition explained kinetically and theoretically are reported that have important significance to researchers. The various effects like ensembles, ligand, and strain on adsorbate (bimetallic material) binding to metal surface was detailed studied [50] in which they explained theoretical studies of H-and O-binding parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobalt ferrite (CoFe 2 O 4 ) with moderate saturation magnetization, high coercivity and Curie temperature, as well as excellent chemical stability has gained increasing attention in technological applications, such as magnetic recording, catalysis, biotargeted drug delivery, magnetic resonance imaging, and spintronics. [1][2][3][4][5][6][7] In general, CoFe 2 O 4 possesses a cubic inverse spinel structure with the Fd 3m space group,in which Co 2+ ions predominantly occupy octahedral B sites and Fe 3+ ions are almost equally distributed between tetrahedral A and octahedral B sites. However, cation distribution between the A and B sites varies with the chemical composition and synthesis procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This pre-polymer cured using GAP as an azide bearing polymer and the resultant crosslinked network copolymer provides superior processability and improved ballistic properties in terms of large amount of gas generating species during combustion. Zhang et al [19] synthesized azido terminated polyethylene glycol by halogenating reaction and azidation two-step method. And more significantly, the modifier gives a lower glass-transition temperature than parent polymer.…”
Section: Introductionmentioning
confidence: 99%